Gross Human Rights Violations Of Slavery And Human Abuse In Cages In Lagkat District (Analysis of Stabat District Court Decision Number 467/Pid.B/2022/PN Stb) - Riki Hamdany; Yasmirah Mandasari Saragih; Rahmayanti, Rahmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The state must respect, cherish, and protect human rights as a legal instrument. Humanity itself possesses the right to live, not to be tortured, and never to be enslaved. With the provisions on human rights and the punishment of human trafficking, everyone enjoys legal protection from acts of degrading human dignity. As described in the provisions of the Law on the Prohibition of Slavery in Indonesia, this is regulated in some of the laws applicable nationally in the country of Indonesia. This prohibition on slavery, or slavery, can be found in Law No. 39 of 1999 on Human Rights in the section that explains a few of the human prohibitions on non-slavery, namely Article (4), Article (20), and in Article (2) of the Act No. 21 of 2007 on the Trafficking in Persons. The case of a human skull in Langkat, North Sumatra, is a terrible crime against humanity. The victims clearly experienced practices of violence, torture, deprivation of rights, and similar acts of human slavery. Reports and facts on the ground show evidence that leads to systematic and structured crime, committed deliberately by the government apparatus. The perpetrators have violated the provisions of Act No. 39 of 1999 on Human Rights and also those contained in Law No. 21 of 2007 on the Suppression of the Crime of Trafficking in Persons; explicitly, this act is in accordance with the meaning of human trafficking. There's a lot of people around, even officials who know where they are and what's going on inside the cage. But they 'proclaim' the condition. No one has attempted to counter the occurrences in the Rare Non-Active House for years. The surrounding society becomes a majority silent, or'majority quiet' over the phenomenon. Neither of the victims, they nor their families, have any basic knowledge of their rights, so that only "sacracy" can be done. They assume they made a mistake and deserve punishment. The company's owners physically hardened them for years, solely for their economic benefit.